2011
DOI: 10.5152/dcbybd.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Intoxication Cases in the ICU

Abstract: Aim: In this study, we aimed to analyse the epidemiological and demographic features, prognosis and length of stay of patients admitted to the hospital ICU with poisoning over a two-year period. Materials and Methods: Patients accepted to the ICU with poisoning from 1 January, 2008-1 January, 2011 were evaluated according to their demographic characteristics, ethology, admission time to emergency service and length of stay in the ICU. Results: Seventy-six (70.4%) of 108 patients who were accepted to the ICU wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 11 publications
2
18
3
5
Order By: Relevance
“…The lenghts of stay in intensive care unit were found to be similar to the literature in this study (12,26,27). No patient was lost.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The lenghts of stay in intensive care unit were found to be similar to the literature in this study (12,26,27). No patient was lost.…”
Section: Discussionsupporting
confidence: 77%
“…Again, Gündüz et al (13) found that 77% of intoxication cases related with suicide attempt were female in their study. Since the data related with patients aged up to 18 years were included in this study, it was found that the intoxication cases related with suicide attempt clustered in the age group of 14-18 years similar to the results of Özayar et al (12) and the girls in this age group who were intoxicated had ingested a substance to commit suicide.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations